2012
DOI: 10.1124/mol.111.076745
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Breast Cancer Resistant Protein by Peroxisome Proliferator-Activated Receptor α in Human Brain Microvessel Endothelial Cells

Abstract: Breast cancer resistance protein (BCRP/ABCG2), an ATP-binding cassette (ABC) membrane-associated drug efflux transporter, is known to localize at the blood-brain barrier (BBB) and can significantly restrict xenobiotic permeability in the brain. The objective of this study is to investigate the regulation of BCRP functional expression by peroxisome proliferator-activated receptor alpha (PPAR␣), a ligand-activated transcription factor primarily involved in lipid metabolism, in a cerebral microvascular endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 42 publications
5
36
0
Order By: Relevance
“…BCRP has been reported to be modulated by a number of nuclear receptors including peroxisome proliferator-activated receptor α (PPARα) in human immortalised hCMEC/D3 cells (132,133), nuclear factor kB (NF-kB) in primary (134) and immortalised (hCMEC/D3) (135) brain endothelial cells, pregnane X receptor (PXR) and constitutive androstane receptor (CAR) (136,137), esteogen receptors in rodent brain capillaries (77) (138) and recently the aryl hydrocarbon receptor (AhR) (66, [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
“…BCRP has been reported to be modulated by a number of nuclear receptors including peroxisome proliferator-activated receptor α (PPARα) in human immortalised hCMEC/D3 cells (132,133), nuclear factor kB (NF-kB) in primary (134) and immortalised (hCMEC/D3) (135) brain endothelial cells, pregnane X receptor (PXR) and constitutive androstane receptor (CAR) (136,137), esteogen receptors in rodent brain capillaries (77) (138) and recently the aryl hydrocarbon receptor (AhR) (66, [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
“…3B). Recently, another isoform, PPARα, has also been shown to directly induce ABCG2 mRNA and protein expression through binding to the same conserved enhancer region of the ABCG2 gene in human brain microvessel endothelial cells (Hoque, Robillard, & Bendayan, 2012). In primary human hepatocytes, exposure to certain NR ligands resulted in enhanced ABCG2 mRNA expression, strongly suggesting the regulatory role of the PXR and CAR pathways ( Jigorel et al, 2006).…”
Section: P0305mentioning
confidence: 99%
“…The mouse Sertoli testicular (TM4) and Caco-2 cell lines were obtained from the American Tissue Culture Collection (Manassas, VA). These cells were cultured as described in our previous publications and those of others (24,26,27).…”
Section: Materials Raltegravir and [mentioning
confidence: 99%
“…In addition, raltegravir is reported to have low oral bioavailability in humans (20)(21)(22). Studies from our group and those of others have shown the functional expression of several ABC drug efflux transporters, including P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), and multidrug resistance-associated proteins (MRPs), in blood-brain barrier, blood-testicular barrier, and blood-intestinal barrier models, which can collectively serve as a biochemical barrier to drug entry/distribution in these tissues (23)(24)(25)(26)(27). Raltegravir interactions with P-gp and BCRP transporters were recently investigated in a few studies; however, inconsistent results have been reported, depending on the methods used (28)(29)(30).…”
mentioning
confidence: 99%